2020
DOI: 10.1001/jamaoncol.2020.1460
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Leveraging Social Determinants of Health to Improve Breast, Cervical, and Colorectal Cancer Screening

Abstract: IMPORTANCE Screening for breast, cervical, and colorectal cancers in the United States has remained below the Healthy People 2020 goals, with evidence indicating that persistent screening disparities still exist. The US Department of Health and Human Services has emphasized cross-sectoral collaboration in aligning social determinants of health with public health and medical services. Examining the economics of intervening through these novel methods in the realm of cancer screening can inform program planners,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 46 publications
0
41
0
2
Order By: Relevance
“…In contrast, in two studies of patients treated in safety-net hospitals and integrated health care systems with equal access to care, racial disparities were not observed [ 20 , 32 ]. According to two recent systematic reviews, focused interventions to address social determinants of health are needed to improve cost-effective colorectal cancer screening in underserved, vulnerable populations, since factors such as poverty, lack of education, immigration status, lack of social support, and social isolation play a significant role in stage at diagnosis and overall survival [ 33 , 34 ]. Even though race and insurance appear to play a significant role in CRC care delivery and mortality as illustrated in this study, these factors do not fully explain the existing disparities.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, in two studies of patients treated in safety-net hospitals and integrated health care systems with equal access to care, racial disparities were not observed [ 20 , 32 ]. According to two recent systematic reviews, focused interventions to address social determinants of health are needed to improve cost-effective colorectal cancer screening in underserved, vulnerable populations, since factors such as poverty, lack of education, immigration status, lack of social support, and social isolation play a significant role in stage at diagnosis and overall survival [ 33 , 34 ]. Even though race and insurance appear to play a significant role in CRC care delivery and mortality as illustrated in this study, these factors do not fully explain the existing disparities.…”
Section: Resultsmentioning
confidence: 99%
“…These disparities need to be addressed with community engagement. A systemic review of economic evaluations of interventions leveraging social determinants of health to improve breast, cervical, and colorectal cancer screening found that they appear to be cost-effective for underserved, disadvantaged populations in the United States [ 54 ]. Community residents’ and leaders’ engagement as equal partners in structural and systemic interventions is a must for cancer screening programs to address root causes of disparities [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the potential drivers of these disparities could be best conceptualized as social determinants of health (SDOH). In recognizing the importance of SDOH in cancer screening disparities, a recent systematic review highlighted the utility of interventions based on SDOH to promote preventive cancer screening ( Mohan and Chattopadhyay, 2020 ). Systemic racism also likely contributes to the lower cervical cancer screening practices of different racial/ethnic groups, where increasing trust with healthcare providers and implementing person-centered care are critical steps to increase cervical cancer screening uptake ( Fuzzell et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%